PENGARUH LAPORAN KEBERLANJUTAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP COST OF DEBT (STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA YANG MENGUNGKAPKAN SUSTAINABILITY REPORT PERIODE TAHUN 2013-2016) - , HERNINGSIH; , HARIYATI (Jurnal Akuntansi AKUNESA, 2018)
This study aims to examine the influence of sustainability report and institutional ownership on cost of debt with firm size as a control variable. The purposive sampling technique was used to select samples. So that a sample of 134 companies revealed the sustainability report listed on the Indonesia Stock Exchange during the 2013-2016 period. Data analysis techniques. Used in this study is multiple linier regression analysis. Using SPSS software 23. The results of the study show that sustainability reports and institutional ownership do not affect the cost of debt. Information in the form of a sustainability report is considered, by the creditor, only a set of share ownership by institution investors is held by a foreign institution so that supervision is carried out when there is an opportunity. Companies with large sizes usually have a large total assets as well, so they are expected to be able to repay loans and interest in the coming period of formation that is not guaranteed the truth.Keywords : Cost of Debt, Institutional Ownership, Sustainability Report